CHI '09 Extended Abstracts on Human Factors in Computing Systems 2009
DOI: 10.1145/1520340.1520552
|View full text |Cite
|
Sign up to set email alerts
|

Designing interfaces for presentation of opinion diversity

Abstract: News aggregators rely on links and users votes to select and present subsets of the large quantity of news and opinion items generated each day. Opinion diversity in the output sets can provide several benefits. We outline a range of diversity goals and discuss user reactions to a pilot implementation that selects for diversity as well as popularity. We then describe plans for research on alternative presentations and their impacts on users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…However, further research is needed to elucidate how the use of new communication technologies affects a confirmation bias and what the implications are. At the front of technology design, some scholars have found that formal emphasis of attitude-consistent and attitude-discrepant messages affects user responses to an online site (Munson & Resnick, 2010) (see also section "Technology Cues") and work on algorithms to build online aggregators of news and op-ed items that present users with greater diversity without turning them off, in the interest of societal benefits of increased diversity of information and opinion (Munson, Zhou, & Resnick, 2009). …”
Section: Confirmation Biasmentioning
confidence: 99%
“…However, further research is needed to elucidate how the use of new communication technologies affects a confirmation bias and what the implications are. At the front of technology design, some scholars have found that formal emphasis of attitude-consistent and attitude-discrepant messages affects user responses to an online site (Munson & Resnick, 2010) (see also section "Technology Cues") and work on algorithms to build online aggregators of news and op-ed items that present users with greater diversity without turning them off, in the interest of societal benefits of increased diversity of information and opinion (Munson, Zhou, & Resnick, 2009). …”
Section: Confirmation Biasmentioning
confidence: 99%
“…Although this paper does not focus on diversification or bursting the information bubble, its approach of presenting only updates of the news without repeating what the user has already read may indeed cause it to present diverse information to users. Munson et al (2009aMunson et al ( , 2009b addressed diversifying news aggregators according to political orientations (see Section 5.4.5). Yom-Tov et al (2014) focused on increasing exposure to different political opinions and discussed the role of language models (Zhai 2008) on people's exposure to opposing viewpoints.…”
Section: Diversificationmentioning
confidence: 99%
“…He hypothesized that Internet use would lead to increased polarization among the public as it makes it easier for people to seek information and opinions, and form camps, with like-minded others. In channeling Sunstein's hypothesis, several scholars have examined how to mitigate polarization [52,40,42,41,60,18,17]. In the sections that follow, we first present empirical research on online communities and polarization, discuss the challenges and limits of this literature, and finally, review how the common design agenda is based on only a partial perspective on polarization in online communities.…”
Section: Background the Social Implications Of Polarizationmentioning
confidence: 99%
“…Since polarization is considered harmful for society, research in HCI and related disciplines has examined how to mitigate it through design endeavors [52,40,42,41]. While there is research indicating that echo chambers are not always a result of underlying technology design decisions or algorithmic bias but rather on group processes [46,24,11], the work has been focused on "nudging" the users and applying behavioral change techniques.…”
Section: How Hci Has Aimed To Mitigate Polarization?mentioning
confidence: 99%
See 1 more Smart Citation